The Effect of Employee Commitment, and Motivation, on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable Study at PT Bank Mega, TBK Manado Area (International Journal of Scientific Research and Management (IJSRM), 2022)
Companies are required to optimize human resources. This study intends to determine the magnitude of the impact of employee commitment, and motivation, on employee performance through organizational citizenship behavior segmentally or simultaneously at PT Bank Mega, TBK Manado area. The sample used was 64 employees of PT Bank Mega, TBK Manado area, with data collection using a questionnaire. Technical statistical analysis using Path Analysis with SPSS software application program version 2.4. The consequences of this study make sense that worker responsibility straightforwardly affects hierarchical citizenship conduct, representative inspiration straightforwardly affects hierarchical citizenship conduct, worker responsibility straightforwardly affects worker execution, representative inspiration straightforwardly affects worker execution, hierarchical citizenship conduct straightforwardly affects worker execution, the representative obligation to representative execution through authoritative citizenship conduct has no interceding impact, and inspiration on worker execution through hierarchical citizenship conduct has an intervening impact.